An Unprecedented Class of Benzoyldiazenido‐Functionalized Polyoxometalates with Enhanced Antitumour Activities. Issue 46 (11th December 2017) - Wang, Longsheng; Yin, Panchao; Zhang, Jin; Xiao, Fengping; Fang, Zhikun; Fu, Weiwei; Wei, Yongge; Xue, Shijia
Abstract : An unprecedented class of benzoyldiazenido‐functionalized polyoxometalates, [Bu4 N]3 [Mo6 O18 (=N=NCOAr)] (Ar=Ph, 1 ; Ph‐ o ‐Cl, 2 ; Ph‐ m ‐Cl, 3 ; Ph‐ p ‐Cl, 4 ; Ph‐ o, p ‐Cl2, 5 ; Ph‐ p ‐Br, 6 ; Ph‐ m ‐NO2, 7 ; Ph‐ p ‐NO2, 8 ; Ph‐ p ‐OMe, 9 ), are prepared through the reactions of α‐octamolybdate and the corresponding hydrazides in dry acetonitrile under reflux with dicyclohexylcarbodiimide (DCC) as a dehydrating agent. Single‐crystal X‐ray diffraction structural analysis reveals that their anions demonstrate the typical structural features of monofunctionalized hexamolybdates with different organic substituents. 1 H NMR spectroscopy indicates that the [Mo6 O18 (NN)] fragments in these compounds are electron‐donating groups rather than electron‐withdrawing groups, and this behaviour was further validated by the calculation of the atomic‐charge distributions [natural bond orbital (NBO) and Mülliken]. Cyclic voltammetry (CV) indicates that they are more difficult to reduce than hexamolybdate and its organoimido derivatives. Antitumour activity tests against K562 show that most of the hybrid compounds have enhanced inhibitory activities compared with those of hexamolybdate and the corresponding hydrazide ligands. Abstract : An unprecedented class of benzoyldiazenido‐functionalized polyoxometalates (POMs) are prepared and characterized thoroughly. Antitumoral activity tests against K562 cells show that these compounds have enhanced inhibitory activity against K562 cell compared to the parent cluster and the corresponding hydrazide ligands.